Periprosthetic joint infection due to Brucella infection: A report of a rare presentation and review of the literature - Mahmoud Jabalameli,; Abolfazl Bagherifard,; Mohammad Taher Ghaderi,; Paniz Motaghi,; Hossein Akbari Aghdam, (Indian Journal of Case Reports, 2021)
Periprosthetic infection (PJI) is a serious complication of total knee arthroplasty (TKA). PJI due to Brucellosis is a very rare entity. In this report, we described the case of knee joint loosening after TKA in a 63-year-old female who arrived with complaints of a restricted range of motion, stiffness, and pain. The diagnosis was made based on clinical, radiological, and laboratory findings. She was treated with antibiotics and two-stage revision surgery. We also reviewed all similar cases in the English literature from the epidemiologic, diagnostic, and treatment aspects and brought suggestions for evaluations before TKA in endemic areas. Authors emphasize that Brucellosis must be considered among differential diagnoses for patients with PJI, especially in endemic areas. Serologic evaluations and long-term blood and joint aspirated fluid culture must be performed when the patient has a history of recurrent febrile illness, joint swelling, and exposure to animals or the consumption of unpasteurized dairy products. Early suspicion of Brucellosis improves the outcome and prevents medical staff from being infected. A double therapy with doxycycline and rifampin for 6 months and performing two-stage revision surgery is the treatment of choice.